Do venture capital-driven top management changes enhance corporate innovation in private firms? - Yu, Qianqian (Journal of Banking & Finance, 2025)
Using hand-collected data from Form Ds on executives in venture capital (VC)-backed private firms, I show that VC-driven top management changes lead to a significantly greater quantity and quality of innovation, which potentially occurs through new management teams hiring more and higher quality inventors. My evidence demonstrates that both founder replacements and non-founder management changes are associated with enhanced innovation. Further, adding top managers with general managerial skills enhances innovation, whereas changing managers with a prior technical background does not. Finally, top management changes lead to the adoption of an exploitative (rather than explorative) innovation search strategy by private firms.